Examination of Adult Spinal Deformity Patients Undergoing Surgery with Implanted Spinal Cord Stimulators and Intrathecal Pumps. Issue 3 (1st February 2022) - Daniels, Alan H.; Durand, Wesley M.; Steinbaum, Alyssa J.; Lafage, Renaud; Hamilton, D. Kojo; Passias, Peter G.; Kim, Han Jo; Protopsaltis, Themistocles; Lafage, Virginie; Smith, Justin S.; Shaffrey, Christopher; Gupta, Munish; et al.
Abstract : Study Design: Retrospective cohort study of a prospectively collected multi-center database of adult spinal deformity (ASD) patients. Objective: We hypothesized that patients undergoing ASD surgery with and without previous spinal cord stimulators (SCS)/ intrathecal medication pumps (ITP) would exhibit increased complication rates but comparable improvement in health-related quality of life. Summary of Background Data: ASD patients sometimes seek pain management with SCS or ITP before spinal deformity correction. Few studies have examined outcomes in this patient population. Methods: Patients undergoing ASD surgery and eligible for 2-year follow-up were included. Preoperative radiographs were reviewed for the presence of SCS/ITP. Outcomes included complications, Oswestry Disability Index (ODI), Short Form-36 Mental Component Score, and SRS-22r. Propensity score matching was utilized. Results: In total, of 1034 eligible ASD patients, a propensity score-matched cohort of 60 patients (30 with SCS/ITP, 30 controls) was developed. SCS/ITP were removed intraoperatively in most patients (56.7%, n = 17). The overall complication rate was 80.0% versus 76.7% for SCS/ITP versus control ( P  > 0.2), with similarly nonsignificant differences for intraoperative and infection complications (all P  > 0.2). ODI was significantly higher among patients with SCS/ITP at baseline (59.2 vs. 47.6, P  = 0.0057) and at 2-year follow-up (44.4 vs . 27.7, P  = 0.0295). The magnitude of improvement, however, did not significantly differ ( P  = 0.45). Similar results were observed for SRS-22r pain domain. Satisfaction did not differ between groups at either baseline or follow-up ( P  > 0.2). No significant difference was observed in the proportion of patients with SCS/ITP versus control reaching minimal clinically important difference in ODI (47.6% vs . 60.9%, P  = 0.38). Narcotic usage was more common among patients with SCS/ITP at both baseline and follow-up ( P  < 0.05). Conclusion: ASD patients undergoing surgery with SCS/ITP exhibited worse preoperative and postoperative ODI and SRS-22r pain domain; however, the mean improvement in outcome scores was not significantly different from patients without stimulators or pumps. No significant differences in complications were observed between patients with versus without SCS/ITP. Level of Evidence: 3 Abstract : ASD patients undergoing surgery with implanted spinal cord stimulators or indwelling intrathecal pain pumps exhibited worse preoperative and post-operative ODI and SRS-22r pain domain; however, the mean improvement in outcome scores was not significantly different. No significant differences in complications were observed between patients with versus without SCS/ITP.